Pelatihan Digital Marketing Dalam Membentuk Branding Sekolah - Renita Astri; Dio Prima Mulya; Putri Anggraini; Sularno Sularno; Zulfahmi Zulfahmi; Faradika Faradika (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
The pandemic situation demands very fast and significant changes in various fields including education. Teachers as human resources in schools must be able to follow dynamic changes by adapting according to the development of developing technology fast. The pandemic has caused a decrease in the number of students attending school, because of school implementing study from home so that many prospective students postpone going to school. This matter becomes a problem for the school to maintain its existence, therefore the team devotion to carry out community service by providing training and mentoring. The result is: the training goes well with the formation of SOPs and examples creation of social media to show the uniqueness of Miftahul Huda Superior Islamic Elementary School the.